Hubungan Tingkat Activity Daily Living (ADL) dan Kualitas Hidup Lansia di Magetan - Rinandha Yusfahreza Wildhan; Rivan Virlando Suryadinata; Ida Bagus Made Artadana (Universitas Wijaya Kusuma Surabaya, 2022)
Most chronic diseases begin to appear in the elderly. Physiological decline in the elderly will also have an impact on the daily activities of the elderly. Dependence on other people is needed by most of the elderly in carrying out daily activities. This will directly affect the quality of life for the elderly. This study aims to analyze the relationship between the level of Activity Daily Living (ADL) and quality of life in the elderly group in Magetan. This research method is observational using a sample of 80 elderly people. Data were collected by purposive sampling in accordance with the inclusion and exclusion criteria in the study. The daily activity assessment process uses the Activity Daily Living (ADL) questionnaire, while the quality of life assessment also uses a questionnaire which is divided into four domains (physical, psychological, social and environmental). The research data obtained will be tested for correlation using the Spearman test. The results of the Spearman test analysis showed that there was a positive correlation between Activity Daily Living (ADL) on the four domains (physical, psychological, social and environmental) on quality of life (p<0.05). In the four domains, there was a relationship (correlation) with ADL, namely the physical domain (r=0.560), psychological domain (r=0.463), social domain (r=0.415), environmental domain (r=0.340). So it can be concluded that there is a relationship between Activity Daily Living (ADL) on the four domains, namely physical, psychological, social and environmental. However, the physical domain has the greatest influence on the daily activities of the elderly.